How technology-based firms become also highly innovative firms? The role of knowledge, technological and managerial capabilities, and entrepreneurs' background - Sergio Camisón-Haba; Jose A. Clemente-Almendros; Tomas Gonzalez-Cruz (Journal of Innovation & Knowledge (JIK), 2019)
To what extent is the likelihood that a Technology-Based Firm - TBF - turns into a Technology-Based and Highly Innovative Firm - TB&InnF - is influenced by technical capabilities or managerial capabilities and education background? We analyse this question using a novel data panel assembled for 326 Spanish industrial firms, along the period 1998-2014. Our findings show the probability of becoming a TB&InnF growths when firms are able to accumulate a high endowment of knowledge and technological capabilities, and a managerial team with experience, a strong power position and previous technical or managerial education background. Results also indicate the CEO's educational profile in management is preferable to a pure technical background by facilitating the transformation into a TB&InnF, because it complements better with the firm's knowledge and technological capabilities by facilitating the transformation of a scientific or technological project into a successful entrepreneurial innovation, which creates new value. These findings make a clear distinction between TBF and TB&InnF, put in question the traditional definition of TB&InnF, exclusively focused toward R+D activity, and valorise the importance of a CEO with both a broader vision that combines technologies, products, markets and people, with the ability to sense and seize new opportunities.
Keywords: 650; Entrepreneurial education; Knowledge-based capabilities; Managerial capabilities; Technological capabilities; Technology-Based & Highly Innovative Firm